Barriers to implementation of the (SA) National Cybersecurity Policy Framework - Gwala, Sizwe (My University, 2016)
Technological advancement have seen South African government departments, state owned entities and private companies using cyberspace as a platform of interaction and the storage of information. Technological advancements have a positive impact due to the compression of space, time and thereby ensuring fastpaced interaction across borders. These technological advancements have, however resulted in most organisations, both private and public, becoming prone to cybercrimes and related incidents. In an initiative aimed at countering these threats, the South African government has passed various laws. The National Cybersecurity Policy Framework (NCPF) is a South African Policy framework aimed at countering an increase in the occurrence of cybercrimes and related incidents. This research analyses the status in the implementation of the NCPF objectives allocated to the Department of Telecommunications and Postal Services (DTPS). Then the barriers in the Implementation are unpacked guided by the literature reviewed and finally recommendations on how to counter the identified barriers are provided post the data collection. The report firstly provides an outline of the global perspectives on cybersecurity which is followed by the regional cybersecurity measures, and then the national cybersecurity measures proposed by the South African Government department are outlined. The latter parts of the report focuses on the NCPF in terms of its scope, goals, objectives and stakeholders. Finally, focus is shifted to the DTPS as a chosen area of research wherein data was collected in a form of one-on-one, semi-structured interviews with relevant parties. The results of this research are presented as a narrative description that is synthesised to develop the theoretical conjecture and empirical generalisation of the entire research. This research uncovered that there are numerous barriers in the implementation of the NCPF both within the DTPS as well as between the DTPS and various stakeholders entrusted with the implementation responsibility. The last chapter consists of general conclusions made by the researcher based on the research conducted which is then followed by recommended countermeasures which will be communicated to the DTPS as well as all stakeholders who will be affected by the proposed recommendations.
Thesis (M.M. (Security))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2016
Keywords: Cyberspace--Security measures--Government policy--South Africa; Computer crimes--Prevention--Government policy--South Africa